Does Economic Policy Uncertainty Encourage Gambling? Evidence from the Chinese Welfare Lottery Market - Can Xu; Andreas Steiner; Jakob de Haan (Center for Economic Studies and ifo Institute (CESifo), 2023)
This paper investigates the effect of economic policy uncertainty (EPU) on gambling activity in China. Based on a theoretical model, we hypothesize that EPU increases the demand for hope which raises the willingness to pay for lottery tickets, resulting in higher lottery sales. We estimate a Panel Autoregressive Distributed Lag model with an Error-Correction form using data on lottery sales in Chinese provinces to estimate the short- and long-run effect of EPU on gambling. Our results suggest that EPU has a significant positive effect on gambling in the short run. In addition, we find that this positive effect is less persistent if the EPU proxy is based on economic policy reports in national newspapers than when the EPU measure is derived from local newspaper reports. This may be explained by the different thematic focus and the different degrees of media censorship of national and local newspapers.
Keywords: D12; D81; D91; G41; L83; 330; economic policy uncertainty; household behaviour under uncertainty; gambling behaviour; welfare lottery; China